Inquinamento elettromagnetico e salute fra controversie, ricerca indipendente ed associazionismo Il caso del movimento degli elettrosensibili - Milena Greco (EtnoAntropologia, 2017)
This intervention is going to consider the main debate points and controversies connected withthe fallout the rising levels of electromagnetic pollution have on health, within the framework of medical anthropology. After retracing the main terms and viewpoints of the political and scientific debate revolving around these issues, the focus of the debate will move on describing the implications ofelectrohypersensitivity, a contentious syndrome and on the role played by those movements and associations pushing for this illness to be recognized as a debilitating environmental disease.